Exposure to polycyclic aromatic hydrocarbons in women living in the Chinese cities of BaoDing and Dalian revealed by hair analysis - Paul Palazzi; Sakina Mezzache; Nasrine Bourokba; Emilie M. Hardy; Anna Schritz; Philippe Bastien; Claude Emond; Jing Li; Jeremie Soeur; Brice M.R. Appenzeller (Environment International, 2018)
Polycyclic aromatic hydrocarbons (PAH) are produced from incomplete combustion of organic matter and released as environmental contaminants from activities such as transports, wood combustion, coal-fired power plants. In numerous urban areas worldwide, the levels of PAH exposure are considered critical regarding public health issues. The possibility to detect PAH and PAH metabolites biologically incorporated in human hair was demonstrated and proposed as biomarkers of exposure. Nevertheless, the possibility to distinguish different levels of exposure between different populations is still needed to validate the relevance of hair analysis in epidemiological studies. In this work, hair samples were collected from 204 women from two cities in China based on one year Air Quality Index history from governmental data (Baoding as polluted city and Dalian less polluted city). 8 out of the 15 parent PAH and 7 out of the 56 metabolites analyzed in this study were detected in all the samples. The highest concentrations in hair were observed for phenanthrene (4.2 to 889 pg/mg) > fluoranthene (1.05 to 204 pg/mg) > pyrene (3.2 to 124 pg/mg) for parent PAH, and for 9-OH-fluorene (0.04 to 1.78 pg/mg) > 2-OH-naphthalene (0.68 to 811 pg/mg) > 1-OH-anthracene (0.24 to 10.9 pg/mg) for metabolites. 14 parent PAH and 15 metabolites presented a significantly higher concentration in the hair samples collected from Baoding, as compared to Dalian. The median concentration of parent PAH was from 1.5 to 2.8 times higher in the hair of the subjects from Baoding than in subjects from Dalian and that of PAH metabolites was from 1 to 2.3 times higher. The study of inter-chemical associations revealed similarities and differences between the two areas, suggesting common and different sources of exposure depending on PAH respectively. The results confirmed the relevance of hair analysis to identify qualitative and quantitative differences in PAH exposure between populations from different areas. This study is the first one to investigate both parent PAH and their metabolites in a biological matrix. Keywords: Polycyclic aromatic hydrocarbons, Hair analysis, Cumulative exposure, Environmental exposure, Biomarkers